Momordica charantia Administration Improves Insulin Secretion in Type 2 Diabetes Mellitus - Cortez-Navarrete, Marisol; Martínez-Abundis, Esperanza; Pérez-Rubio, Karina G; González-Ortiz, Manuel; Méndez-Del Villar, Miriam (Journal of medicinal food, 2018)
An improvement in parameters of glycemic control has been observed with Momordica charantia in patients with type 2 diabetes mellitus (T2DM). It is unknown whether this improvement is through a modification of insulin secretion, insulin sensitivity, or both. We hypothesized that M. charantia administration can improve insulin secretion and/or insulin sensitivity in patients with T2DM, without pharmacological treatment. The objective of the study was to evaluate the effect of M. charantia administration on insulin secretion and sensitivity. A randomized, double-blinded, placebo-controlled, clinical trial was carried out in 24 patients who received M. charantia (2000 mg/day) or placebo for 3 months. A 2-h oral glucose tolerance test (OGTT) was done before and after the intervention to calculate areas under the curve (AUC) of glucose and insulin, total insulin secretion (insulinogenic index), first phase of insulin secretion (Stumvoll index), and insulin sensitivity (Matsuda index). In the M. charantia group, there were significant decreases in weight, body mass index (BMI), fat percentage, waist circumference (WC), glycated hemoglobin A1c (A1C), 2-h glucose in OGTT, and AUC of glucose. A significant increase in insulin AUC (56,562 ± 36,078 vs. 65,256 ± 42,720 pmol/L/min, P = .043), in total insulin secretion (0.29 ± 0.18 vs. 0.41 ± 0.29, P = .028), and during the first phase of insulin secretion (557.8 ± 645.6 vs. 1135.7 ± 725.0, P = .043) was observed after M. charantia administration. Insulin sensitivity was not modified with any intervention. In conclusion, M. charantia administration reduced A1C, 2-h glucose, glucose AUC, weight, BMI, fat percentage, and WC, with an increment of insulin AUC, first phase and total insulin secretion.